Applications of Geosynthetics to Irrigation, Drainage and Agriculture - Eric Blond; Stan Boyle; Marianna Ferrara; Bruno Herlin; Herve Plusquellec; Pietro Rimoldi; Timothy Stark (Irrigation and Drainage, 2019)
Geosynthetics are man‐made products manufactured to meet specific functions in earthworks and geotechnical projects, such as dams, levees, canals, dikes and other structures commonly found in agricultural engineering. Thanks to the Memorandum of Understanding between the International Geosynthetics Society (IGS) and the International Commission on Irrigation and Drainage (ICID), collaborative efforts are being undertaken to generate awareness of geosynthetics in agriculture. In the Workshop on ‘Applications of geosynthetics to irrigation, drainage and agriculture’ held at the 23rd International Congress of the ICID in Mexico City on 8 October 2017, a group of delegates from the IGS contributed with a series of presentations introducing various functions and applications of geosynthetics. The authors gave an overview of how geosynthetic products are designed and tested to ensure they will fulfil their intended function, focusing on applications to irrigation, drainage and agriculture. A few key considerations were identified as being critical to ensure proper performance of geosynthetic materials, in geotechnical projects in general and in agriculture in particular. The present paper is intended to provide a summary of these presentations. © 2018 John Wiley & Sons, Ltd.